2022
DOI: 10.1101/2022.01.10.475602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionarily stable gene clusters shed light on the common grounds of pathogenicity in the Acinetobacter calcoaceticus-baumannii complex

Abstract: Nosocomial pathogens of the Acinetobacter calcoaceticus-baumannii (ACB) complex are a cautionary example for the world-wide spread of multi- and pan-drug resistant bacteria. Aiding the urgent demand for novel therapeutic targets, comparative genomics studies between pathogens and their apathogenic relatives shed light on the genetic basis of human-pathogen interaction. Yet, existing studies are limited in taxonomic scope, sensing of the phylogenetic signal, and resolution by largely analyzing genes isolated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 147 publications
(277 reference statements)
0
13
0
Order By: Relevance
“…As virulence factors could differ among isolates, we assessed the distribution of invL across the Acinetobacter genus. Specifically, we performed a targeted ortholog search for invL and adjacent genes in 3,052 available genomes from the National Center for Biotechnology Information (NCBI) RefSeq Database ( 65 ). In genomes that encode InvL, the corresponding gene is flanked by genes encoding a TIGR01244 family phosphatase (D1G37_04390 in UPAB1) and a dihydrolipoyl dehydrogenase (D1G37_RS04400 in UPAB1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As virulence factors could differ among isolates, we assessed the distribution of invL across the Acinetobacter genus. Specifically, we performed a targeted ortholog search for invL and adjacent genes in 3,052 available genomes from the National Center for Biotechnology Information (NCBI) RefSeq Database ( 65 ). In genomes that encode InvL, the corresponding gene is flanked by genes encoding a TIGR01244 family phosphatase (D1G37_04390 in UPAB1) and a dihydrolipoyl dehydrogenase (D1G37_RS04400 in UPAB1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ortholog searches were performed across a database of 3,052 Acinetobacter genomes obtained from NCBI RefSeq as previously described ( 65 ). Briefly, the collection of orthologous groups that resulted from an all versus all ortholog search using OMA was screened to associate the group that harbors a particular protein sequence of interest ( 108 ).…”
Section: Methodsmentioning
confidence: 99%
“…As virulence factors could differ among isolates, we assessed the distribution of InvL across the Acinetobacter genus. Specifically, we performed a targeted ortholog search for invL and adjacent genes in 3052 available genomes from the N ational C enter for B iotechnology Information (NCBI) RefSeq Database (64). In genomes where InvL is encoded, the corresponding gene is flanked by genes encoding a TIGR01244 family phosphatase (D1G37_04390 in UPAB1) and a dihydrolipoyl dehydrogenase (D1G37_RS04400 in UPAB1) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins of interest comprise the translated sequences of D1G37_RS04395 (InvL), D1G37_RS0440, D1G37_RS04390, and A1 S_3863. Since the subset of genomes used by Djahanschiri et al did not include the strain UPAB1, the orthologs identified in the strain MDR-TJ via a reciprocal best blast hit approach were used to associate orthologous groups (64). The resulting presence/absence matrix together with the genus’ phylogeny served as the input for Vicinator v0.32 (https://github.com/BIONF/Vicinator) to trace the microsynteny of the InvL locus based on MDR-TJ and ATCC 17978 as the reference genomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation